Pengaruh Konsentrasi Jahe dan Lama Infusing terhadap Karakteristik Fisik, Kimia, dan Sensori Honey Citron Tea - Lisa Fitri Rahayu; Erni Sofia Murtini (Universitas Bumigora, 2026)
Honey citron tea is a honey-based functional beverage with the potential to support the diversification of honey products in Indonesia. This study aims to analyze the effects of adding ginger (Zingiber officinale) and varying infusion times on the sensory, physical, and chemical characteristics of honey citron tea. The research method used was a two-factor completely randomized design (CRD), with ginger concentration (10%, 15%, 20% w/w) and infusion time (1 and 7 days) as the factors. Sensory data were analyzed using ANOVA, followed by the BNT or DMRT test at a 5% significance level. The results showed that the combination of 15% ginger and a 1-day infusion time was the best treatment based on panelists’ acceptance ratings. The best product-the concentrated honey citron tea sample-had antioxidant activity (IC50) of 930.90 ppm, vitamin C of 0.38 mg/100 g, total sugar of 43.19%, pH of 4.46, moisture content of 35.47%, total soluble solids of 65.33 oBrix, and viscosity of 4436 cPs. In conclusion, ginger concentration and infusion time had a significant effect on all sensory parameters, except for the color of the honey citron tea. These findings have the potential to support the development of honey-based functional beverages utilizing local food ingredients.